Community Based Seed Multiplication - International Potato Center (International Food Policy Research Institute, 2015)
This data study contains field trial data on crop management, yield, farmers field school (FFS) attendance. Project title: Decentralized System for Community-Based Seed Production and Extension Provision. Project abstract: Unavailability of quality seed of commonly grown crops was one of the priority constraints to increased agricultural productivity identified during the PCA. It is the aim of this activity to develop a system whereby this bottleneck can be addressed in a sustainable manner, as far as possible relying on private initiative and community interest rather than be dependent on extension / input support provided by BoAs line agencies and/or NGOs. The approach will work closely with the Model/Lead Farmer concept (1 to 5) which is widely promoted by the GoE with a Farmer Field School (light) approach, that promotes farmer-to-farmer extension. Project website: http://africa-rising.net